Shoulder Arthroplasty Trials Are Infrequently Registered: A Systematic Review of Trials. - Matthew Thomas Sims; Zachary Carter Sanchez; James Murphy Herrington; James Barrett Hensel; Nolan Michael Henning; Caleb Josiah Scheckel; Matt Vassar (PLoS ONE, 2016)
With the intent of improving transparency in clinical research, the International Committee of Medical Journal Editors (ICMJE) established guidelines in 2005 regarding prospective clinical trial registration. This action worked to address bias related to selective outcome reporting in the medical literature. The objective of this study was to assess and characterize the quality of registration of clinical trials appearing in shoulder arthroplasty-related medical journals.All randomized trials involving human subjects, pertaining to shoulder arthroplasty, published between July 1, 2005 and December 31, 2015, and indexed in either PubMed or SportDISCUS were analyzed. We assessed the prevalence of registration, the timing of registration relative to patient enrollment periods, and the variable rates of orthopedic journal compliance with ICMJE and Food and Drug Administration clinical registration standards for our study.Of the 382 articles identified, 345 (90.3%) were excluded due to failure to meet inclusion criteria. From the remaining 37, only 12 (32.4%) studies were found to be registered in a trial registry. Ten (10/12, 83.3%) of these provided their registration information within the body of the article. None of the included studies from ICMJE-recognized journals were registered. From 34 included studies from non-ICMJE recognized journals, 12 (35.3%) were registered.The level of compliance with clinical trial registration guidelines in the decade since their release among shoulder arthroplasty trials in orthopedic journals is poor. Given the importance of the issue, the prevalence of the problem, and the fact that many other medical specialties have already made efforts to improve ICMJE compliance, further work on the part of orthopedic surgery journal authors and editors is needed to ensure the publication of unbiased results.UMIN000022487.